Korean Red ginseng prevents endothelial senescence by downregulating the HO-1/NF-κB/miRNA-155-5p/eNOS pathway - Kim, Tae-Hoon (J Ginseng Res, 2021)
BACKGROUND: Korean Red ginseng extract (KRGE) has beneficial effects on the cardiovascular system by improving endothelial cell function. However, its pharmacological effect on endothelial cell senescence has not been clearly elucidated. Therefore, we examined the effect and molecular mechanism of KRGE on the senescence of human umbilical vein endothelial cells (HUVECs). METHODS: HUVECs were grown in normal or KRGE-supplemented medium. Furthermore, they were transfected with heme oxygenase-1 (HO-1) gene or treated with its inhibitor, a NF-κB inhibitor, and a miR-155-5p mimic or inhibitor. Senescence-associated characteristics of endothelial cells were determined by biochemical and immunohistochemical analyses. RESULTS: Treatment of HUVECs with KRGE resulted in delayed onset and progression of senescence-associated characteristics, such as increased lysosomal acidic β-galactosidase and decreased telomerase activity, angiogenic dysfunction, and abnormal cell morphology. KRGE preserved the levels of anti-senescent factors, such as eNOS-derived NO, MnSOD, and cyclins D and A: however, it decreased the levels of senescence-promoting factors, such as ROS, activated NF-κB, endothelial cell inflammation, and p21 expression. The beneficial effects of KRGE were due to the induction of HO-1 and the inhibition of NF-κB-dependent biogenesis of miR-155-5p that led to the downregulation of eNOS. Moreover, treatment with inhibitors of HO-1, NF-κB, and miR-155-5p abolished the anti-senescence effects of KRGE. CONCLUSION: KRGE delayed or prevented HUVEC senescence through a signaling cascade involving the induction of HO-1, the inhibition of NF-κB-dependent miR-155-5p biogenesis, and the maintenance of the eNOS/NO axis activity, suggesting that it may protect against vascular diseases associated with endothelial senescence.